Factor Analysis Of Class VII Students' Low Interest In Learning In The Subject Of Characteristics At Nurul Fajar IT SMP School Medan - Yusrawani Sinaga, Suci; Ginting, Nurman (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2024)
This article discusses the analysis of students’ low interest as the factor in akidah akhlak learning subjects. Research method used was a qualitative method. Purpose of the study was to discover in-depth and try to find out the meaning that underlind the students’ interest in akidah akhlak learning subject. Results of this study are: (1) The internal factors, lack of interest and motivation of learners during the learning of Akidah Akhlak; (2) External factors, methods of teaching and teachers who did not appeal to learners.